Stödbevisning i våldtäktsmål – ett indirekt krav? - Ermanno Fäldner,Vera (2023)
According to current Swedish law, the court shall be free to examine the evidence adduced. It must therefore be possible for the court to consider a course of events established beyond reasonable doubt based solely on the injured party’s testimony. Nonetheless, it is possible to conclude from case law that this is rarely sufficient and that, to fulfil the evidentiary requirement, it is required, to present other evidence that in various ways confirms the information provided by the injured party. The purpose of this essay has been to determine the definition and function of supporting evidence under the law of evidence. The research question has been: What are the legal consequences, for the assessment of the crime of rape, arising from the adoption of the definition and function of supporting evidence in relation to the threshold of evidence in criminal proceedings? To answer the question, an evaluation has been conducted based on doctrine as well as an analysis of the assessment presented by the Supreme Court in rape cases where words stand against words. Based on the study conducted, it can be concluded that the Supreme Court has used differing formulations regarding what is required for the evidence threshold to be fulfilled. Based on this, it has been found that there is an inconsistency regarding the function and definition of supporting evidence in such a manner that the evidence is not consistently placed in relation to the evidence theme. As a result, I have reached the conclusion that the function of the evidence referred to as supporting evidence is to be considered as an indirect condition for the threshold of evidence to be met. Furthermore, the essay has described how such a requirement is to be regarded as contrary to the principle of free assessment of evidence and what legal consequences of such a demand results in. This includes the identification that the implementation creates formal obstacles regarding the assessment of the main evidence, that a problem arises regarding the requirement of objectivity imposed on the court, as well as creates a schematic assessment of how a crime victim should act.
Keywords: allmän rättslära; straffrätt; bevisvärdering; stödbevisning; våldtäkt